Are you trying to be funny? Communicating humour in deafblind conversations. (October 2019) - Willoughby, Louisa; Manns, Howard; Iwasaki, Shimako; Bartlett, Meredith
Humour is a prevalent feature in any form of human interaction, regardless of language modality. This article explores in detail how humour is negotiated in conversations among deafblind Australians who are fluent users of tactile Australian Sign Language (Auslan). Without access to the visual or auditory cues that are normally associated with humour (e.g. smiles, laughter, eye crinkles and 'smile voice'), there is a risk that deafblind interactants will misconstrue humorous utterances as serious, or be unsure whether their conversation partner has got the joke. In this article, we explore how humorous utterances unfold in tactile signed interactions. Drawing on Conversation Analytic principles, we outline the ad hoc and more conventionalised signals deafblind signers use to signal amusement. Looking at humour in these conversations contributes to a greater understanding of how humour is conveyed across language modalities and further support for humour's centrality to interactional solidarity.